POLITIK KESEJAHTERAAN; ANALISA KESEJAHTERAAN MASYARAKAT DALAM KONDISI TRIPLE DISRUPTION (KAJIAN PARA PEDANGANG KULINER LOKAL DESA WISATA; ANTARA PELABUHAN RAMBANG DAN DERMAGA KERENG BENGKIRAI) - Pratama, Muhammad Anzarach; Mustikaningsih, Wening (Jurnal Darma Agung; Vol 30 No 3 (2022): DESEMBERDO - 10.46930/ojsuda.v30i3.2223, 2022)
This paper is a research of welfare politics, the focus of this research is related to the condition of society facing triple disruption. The purpose of this research is to find out how the welfare conditions of culinary traders face the disruptions of the industrial revolution, the COVID-19 pandemic and climate change,and what is the strategy of culinary traders to dealing with the disruption conditions of this era.This research is a descriptive qualitative research, using a case study approach.The technique of data collecting in this research is analysis primary data, by using depth interviews with 10 research informants.The result of this research is that the welfare of culinary traders in tourist areas is in a condition of triple disruption, both Rambang Port and Kereng Bengkirai Pier are facing a decline in welfare levels. Disruption that is very influential on welfare is the condition of the COVID-19 Pandemic.